Community Participation in Development of Batik Villages through The Walet Sakti Kebumen Association - Abdul Mufid; Helina Himmatul Ulya (Prosperity: Journal of Society and Empowerment, 2023)
Succsesfull development of the Kebumen batik village in Gemesekti Village requires the participation of batik craftsmen. The potential of Kebumen batik can improve the people's economy. This is proven in the program carried out by the Walet Sakti Association. Paguyuban Walet Sakti is one of the organizations that is intense in improving people's welfare through Kebumen batik. This study aims to determine the process of increasing community participation in the development of batik villages through the Kebumen Walet Sakti Association. This study uses a type of qualitative research with data collection techniques in the form of observation, interviews, and documentation. The results of this study are: first, the process of increasing community participation in the development of batik villages through the Kebumen Walet Sakti Association in Gemsekti Village, Kebumen District, Kebumen Regency as follows: Assessment of Problems (Assessment), Program Planning, Program Implementation, and Evaluation. As for internal supporting factors such as getting support from the Kebumen Regional Government, vision and mission compatibility, high participation, Kebumen batik has branding, and has good relationships between members. The inhibiting external factors are: the lack of marketing knowledge of batik craftsmen through social media. there are fears that batik craftsmen have about product marketing, inadequate quality and quantity of human resources. hard to get raw materials. Entrepreneurial spirit of batik craftsmen is still low.